Introducing career to kindergarten students - Rahajeng Bellinda Nastiti; Edi Purwanta (Research and Social Study Institute, 2019)
Career is a lifelong process that an individual will experience throughout his or her life. In relation to the statement, the study aims at depicting the development of career introduction into the Kindergarten Unit, namely in one of the kindergartens located in the City of Lubuklinggau, Province of South Sumatra. During the conduct of the study, the subjects that had been selected were 8 kindergarten students in the Nursery grade (two- to three-years old), 10 kindergarten students in the Kindergarten One Grade (three- to four-years old) and 2 classroom teachers. The type of the study was a qualitative study and the data were gathered by means of participatory observation. After the data had been gathered, the data were analysed by means of Miles & Huberman qualitative data analysis model. After the study has been conducted, the results show that: (1) the Kindergarten Unit that has served as the research site already has thematic learning about career introduction; (2) the mechanism implementation of the thematic learning has not stimulated the career introduction to the students; (3) the material components of the career introduction have not been in accordance to the knowledge of the ideal career and the needs of the kindergarten students; (4) the readiness of the kindergarten teachers in preparing the learning materials has not been ideal; (5) there have been weaknesses on the media of career introduction which leads to the unideal situations among the kindergarten students; and (6) there should be school support toward the upgrade and the completeness of the thematic learning of the career introduction. Through the conduct of the study, it is expected that the mechanism of ideal career introduction in the school might stimulate information in accordance to the characteristics of the students so that the preferences toward the knowledge of career introduction might be early established for the next period.